2014
DOI: 10.1177/1352458514536252
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of CD8+ effector memory T cells is an early and persistent feature of multiple sclerosis

Abstract: Background:Patients with multiple sclerosis (MS) have a deficiency of circulating CD8+ T cells, which might impair control of Epstein–Barr virus (EBV) and predispose to MS by allowing EBV-infected autoreactive B cells to accumulate in the central nervous system. Based on the expression of CD45RA and CD62L, CD4+ T cells and CD8+ T cells can be subdivided into four subsets with distinct homing and functional properties, namely: naïve, central memory, effector memory (EM) and effector memory re-expressing CD45RA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 30 publications
(47 reference statements)
7
53
1
Order By: Relevance
“…19 The frequencies of LCL-specific CD3 + T cells, CD4 + T cells, CD8 + T cells, CD4 + EM T cells and CD8 + EM/EMRA T cells in the PBMC of patients not having a clinical attack (that is, remission, secondary progressive and primary progressive MS) were significantly lower than in healthy EBV-seropositive subjects (Figure 1b). There was a positive correlation between the frequency of LCL-specific CD8 + EM/EMRA T cells in the PBMC with the frequency of total CD8 + EM/EMRA T cells in the PBMC in patients with MS ( r =0.30, P =0.0004) but not in healthy subjects ( r =0.04, P =0.758; Figure 1c), indicating that the decreased CD8 + T-cell response to EBV is associated with the general deficiency of CD8 + EM/EMRA T cells that occurs in MS. 13 In contrast there was no correlation between the frequency of LCL-specific CD4 + EM T cells in the PBMC and the frequency of total CD4 + EM T cells in the PBMC (data not shown) which is normal in MS. 13 The increased T-cell response to EBV during attacks of MS was most clearly shown by analysing the frequencies of LCL-specific cells within the different T-cell phenotypes. As shown in Figure 1d, the frequencies of LCL-specific cells within the CD3 + T cell, CD4 + T cell, CD8 + T cell, CD4 + EM T cell, CD8 + EM T cell, CD8 + EMRA T cell and CD8 + CM T-cell populations during attacks were all significantly higher than in patients not having an attack (Figure 1d).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…19 The frequencies of LCL-specific CD3 + T cells, CD4 + T cells, CD8 + T cells, CD4 + EM T cells and CD8 + EM/EMRA T cells in the PBMC of patients not having a clinical attack (that is, remission, secondary progressive and primary progressive MS) were significantly lower than in healthy EBV-seropositive subjects (Figure 1b). There was a positive correlation between the frequency of LCL-specific CD8 + EM/EMRA T cells in the PBMC with the frequency of total CD8 + EM/EMRA T cells in the PBMC in patients with MS ( r =0.30, P =0.0004) but not in healthy subjects ( r =0.04, P =0.758; Figure 1c), indicating that the decreased CD8 + T-cell response to EBV is associated with the general deficiency of CD8 + EM/EMRA T cells that occurs in MS. 13 In contrast there was no correlation between the frequency of LCL-specific CD4 + EM T cells in the PBMC and the frequency of total CD4 + EM T cells in the PBMC (data not shown) which is normal in MS. 13 The increased T-cell response to EBV during attacks of MS was most clearly shown by analysing the frequencies of LCL-specific cells within the different T-cell phenotypes. As shown in Figure 1d, the frequencies of LCL-specific cells within the CD3 + T cell, CD4 + T cell, CD8 + T cell, CD4 + EM T cell, CD8 + EM T cell, CD8 + EMRA T cell and CD8 + CM T-cell populations during attacks were all significantly higher than in patients not having an attack (Figure 1d).…”
Section: Resultsmentioning
confidence: 83%
“…The positive correlation between the frequency of LCL-specific CD8 + EM/EMRA T cells in the blood and the frequency of total CD8 + EM/EMRA T cells in the blood in MS indicates that the decreased CD8 + T-cell response to EBV is associated with the general deficiency of CD8 + EM/EMRA T cells that occurs early in the disease and persists throughout its course. 13 In view of the critical role of type I IFN (IFN-α and/or IFN-β) in the generation of CD8 + T-cell memory, 59 one possible mechanism for decreased CD8 + T-cell memory in MS is the diminished production of type I IFN that occurs in this disease. 60, 61 Another important question is why the CD8 + T-cell deficiency impairs the response to EBV but not to CMV.…”
Section: Discussionmentioning
confidence: 99%
“…MS GWAS [2] identified risk genes are predominantly expressed in other immune cell subsets [10]; and the success of B cell specific therapies [35], and master-regulation of other immune cell types by myeloid cells [36] support their fundamental roles in MS. Eomes and Tbet are most highly expressed by NK cells, which have already been implicated as pathogenically significant, in that their numbers are reduced in MS [37] and their killing of activated T cells and macrophages [38] is important in therapy. It was recently reported that the CD8 effector memory population (both CD45RA+ and CD45RA-) is also deficient in MS, and that this is an early and persistent feature [39], possibly also contributing to the reduction in Eomes and Tbet in MS peripheral blood, and consistent with a longitudinally stable phenotype. In each individual one or a number of immune cell subsets may be abnormal.…”
Section: Discussionmentioning
confidence: 90%
“…There is thus a convergence of epidemiological, clinical, and immunological evidence that anti-EBNA1 antibodies and CD4+ positive EBNA1-specific T cells cross-reacting with myelin antigens contribute to the pathological process in MS. CD4+ T cells recognizing other EBV antigens and myelin epitopes have also been reported in blood (Lang et al 2002) and the cerebrospinal fluid (Holmoy and Vartdal 2004). These findings do not exclude an important role for EBV-specific CD8+ T cells, although comparisons of their frequency and function in blood and cerebrospinal fluid (CSF) from individuals with MS and matched healthy controls have given somewhat mixed results, which could be in part attributable to methodological differences (Hollsberg et al 2003;Gronen et al 2006;Jilek et al 2008Jilek et al , 2012Jaquiery et al 2010;Angelini et al 2013;Pender et al 2014a;Lossius et al 2014). B cells must also play an important role, either through their antigen-presentation activity or other mechanisms.…”
Section: Potential Mechanisms Relating Ebv To Msmentioning
confidence: 89%